2019
DOI: 10.1021/acs.cgd.9b00954
|View full text |Cite
|
Sign up to set email alerts
|

Putting Fullerenes in Their Place: Cocrystallizing C60 and C70 with Phosphangulene Chalcogenides

Abstract: The distinctive conical shape and electron-rich aromatic surface of phosphangulene (1) and its derivatives offer a geometric and electronic complement to the convex electron-poor surface of fullerenes such as C60 and C70. In crystals of phosphangulene itself, molecules form π-stacks that are efficiently packed. In contrast, the corresponding oxide (2a), sulfide (2b), and selenide (2c) have an awkward shape that prevents effective stacking and forces crystallization to produce structures with abnormally large i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…One possible way to manipulate organization is by using shape-complementary additives, such as derivatives of phosphangulene. 10,16 By focusing on the conical shape of phosphangulene, previous work has not fully exploited other useful properties of the compound. In particular, researchers have largely overlooked its ability to form complexes with transition metals, which offers a simple way to create complex molecular structures with curved aromatic surfaces for binding fullerenes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…One possible way to manipulate organization is by using shape-complementary additives, such as derivatives of phosphangulene. 10,16 By focusing on the conical shape of phosphangulene, previous work has not fully exploited other useful properties of the compound. In particular, researchers have largely overlooked its ability to form complexes with transition metals, which offers a simple way to create complex molecular structures with curved aromatic surfaces for binding fullerenes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Each bound phosphangulene can surround only about one-fourth of the total surface of C 60 , as shown by the structures of cocrystals of phosphangulene chalcogenides with fullerenes. 10 As a result, complexes of phosphangulene are well designed to interact with neighboring fullerenes without completely enveloping them. In contrast, many previous efforts to devise suitable partners for binding fullerenes have targeted ways to surround them.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wuest et al reported X-ray crystal structures of various polymorphs of phosphangulene chalcogenides 116.2a – c 235 and those of the various solvates originating from the cocrystallization of 116.2a – c with C 60 or C 70 . 236 Furthermore, they characterized the crystal structures of the bis(phosphangulene)iminium salts (including [ 116.9 ][Br]) 237 and the silver(I) ( 116.10 + ) and copper(I) ( 116.11 + ) complexes featuring a metal center that is tetracoordinated by phosphangulene ( Scheme 116 ). 238 …”
Section: Pyrenoidsmentioning
confidence: 99%